Epidermis‐Inspired Wearable Piezoresistive Pressure Sensors Using Reduced Graphene Oxide Self‐Wrapped Copper Nanowire Networks. Issue 1 (15th December 2021) - Zhu, Yangzhi; Hartel, Martin C.; Yu, Ning; Garrido, Pamela Rosario; Kim, Sanggon; Lee, Junmin; Bandaru, Praveen; Guan, Shenghan; Lin, Haisong; Emaminejad, Sam; de Barros, Natan Roberto; Ahadian, Samad; et al.
Abstract: Wearable piezoresistive sensors are being developed as electronic skins (E‐skin) for broad applications in human physiological monitoring and soft robotics. Tactile sensors with sufficient sensitivities, durability, and large dynamic ranges are required to replicate this critical component of the somatosensory system. Multiple micro/nanostructures, materials, and sensing modalities have been reported to address this need. However, a trade‐off arises between device performance and device complexity. Inspired by the microstructure of the spinosum at the dermo epidermal junction in skin, a low‐cost, scalable, and high‐performance piezoresistive sensor is developed with high sensitivity (0.144 kPa ‐1 ), extensive sensing range ( 0.1–15 kPa), fast response time (less than 150 ms), and excellent long‐term stability (over 1000 cycles). Furthermore, the piezoresistive functionality of the device is realized via a flexible transparent electrode (FTE) using a highly stable reduced graphene oxide self‐wrapped copper nanowire network. The developed nanowire‐based spinosum microstructured FTEs are amenable to wearable electronics applications. Abstract : A epidermis‐inspired wearable piezoresistive pressure sensors using reduced graphene oxide self‐wrapped copper nanowire networks (CurGONW‐SMPS) exhibit a high sensitivity, extensive sensing range, and good long‐term stability. This CurGONW‐SMPS can be used for real‐time monitoring of human motions and subtle physiological signals.